Organization of mobile network technology based MPLS - Клименко, И. А.; Ткаченко, В. В.; Аленина, Н. А. (Problems of Informatization and Control, 2008)
Technology MPLS - Multiprotocol new technology that combines the tools 1P routing , flow control mechanisms , diffirintsirovanie services and support for QoS. The purpose of the article to show how MPLS technology is used in mobile computer networks for the transmission of data streams to ensure the quality of services